Bronchoscopic lung cryobiopsy for the diagnosis of pulmonary alveolar proteinosis in a hypoxemic patient - Vikas Marwah; C D S Katoch; P Sengupta; Saikat Bhattacharjee (Lung India, 2020)
Pulmonary alveolar proteinosis (PAP) is a rare disorder characterized by the intra-alveolar accumulation of surfactant due to macrophage dysfunction or the production of abnormal surfactant. Diagnosis is usually confirmed by lung biopsy either bronchoscopically or by video-assisted thoracoscopic surgery. Bronchoscopic lung cryobiopsy (BLC) is increasingly being utilized for the histopathological diagnosis of diffuse parenchymal lung diseases; however, it has rarely been reported for PAP. We report a case of 59-year-old male who presented to our center with gradually worsening breathlessness and cough of 1-year duration. Chest radiograph revealed bilateral extensive pulmonary infiltrates and high-resolution computerized tomography scan revealed extensive bilateral ground-glass opacities with areas of sparing. BAL and transbronchial lung biopsy failed to confirm the diagnosis; hence, BLC was done which revealed pathologic findings suggesting PAP. BLC appears to be a promising diagnostic tool for the diagnosis of PAP and offers several diagnostic advantages compared to conventional techniques.